Effect Of Rooftop Rainwater Harvesting Storage Orientation On The Stability Of A High Rise Building - Cheong, Moon Fu (Universiti Sains Malaysia, 2005)
The scope of this study is focussed on the effect of different rooftop rainwater harvesting storage orientations on the structural stability of a high rise building. An existing high rise building in urban area is selected. The high rise building is 77.0 m in height and 59.35 m x 22.75 m in plan. The wind load on the high rise building is calculated by referring to MS 1553:2002. Supply Side Approach is used to size the storage tanks. The high rise building is modelled and analysed by computer software – EsteemPlus 6.2. From this project, it is found that the deflection of the high rise building varies with the orientation of the RRWH storage tank installation. The results also show that rainwater harvesting storage tank installation in high rise building is likely to reduce the impact of wind action if the storage tank is placed near to the centre of the building. However, it is essential to analyse the behaviour of a building before installing any rainwater harvesting storage tank.